2022
DOI: 10.1111/imj.15090
|View full text |Cite
|
Sign up to set email alerts
|

Differences in retinopathy prevalence and progression between Anglo‐Celt and Aboriginal Australians: the Fremantle Diabetes Study Phase II

Abstract: Background: Indigenous populations have higher rates of diabetes and diabetic complications, yet there is a paucity of contemporary data on diabetic retinopathy (DR) prevalence and incidence in urban dwelling Aboriginal Australians. Aims:The aim of the study was to compare the prevalence of DR and incidence of new or worsening DR between Aboriginal Australians and Anglo-Celts with Type 2 diabetes.Methods: Participants from the community-based Fremantle Diabetes Study Phase II (817 Anglo-Celts, 94 Aboriginal pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The National Eye Health Survey and the Fremantle Diabetes Study II both found higher DR prevalence amongst Indigenous participants. 7,8 Considering methodological differences between studies, consistency of within-study comparisons amongst high-quality studies adds strength to our conclusions.…”
Section: J O U R N a L P R E -P R O O F Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…The National Eye Health Survey and the Fremantle Diabetes Study II both found higher DR prevalence amongst Indigenous participants. 7,8 Considering methodological differences between studies, consistency of within-study comparisons amongst high-quality studies adds strength to our conclusions.…”
Section: J O U R N a L P R E -P R O O F Discussionmentioning
confidence: 79%
“…Of these, 15 studies enrolling 8219 diabetic participants were included in our systematic review and metaanalysis. 7,8,[24][25][26][27][28][29][30][31][32][33][34][35][36]…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Future studies may need to study these potential ethnic differences in greater detail. It is likely that the higher rates of DR in Oceanians are related to many of the same ethnic-specific factors that underlie the higher rates in Indigenous Australians, 22 such as low income, less access to quality food and diabetes medical care, and other culture-specific health behaviours. These areas may need to be studied further in order to reduce the gap in DR rates between different ethnic groups.…”
Section: Open Accessmentioning
confidence: 99%
“…Diabetic retinopathy was assessed according to the modified Airlie House Classification system for the Early Treatment Diabetic Retinopathy Study. 16,17 As the original grader was unavailable, follow-up fundus photographs were first assessed independently by an experienced ophthalmologist under the same system used for the baseline images. A second ophthalmologist (AT) graded all photographs assessed as showing DR by the first, and he also graded a randomly-selected sample of the remaining images.…”
Section: Retinopathy Assessmentmentioning
confidence: 99%